Investment Demand on the Bullion Market - Mamcarz, Katarzyna (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
Gold and silver are two precious metals which have been a part of human civilization for centuries. The demand for these metals has been present on more than one market, with the investment demand playing a special role. The goal of the article is to characterize the investment demand on the bullion market and to identify and evaluate the reasons for its development and dynamics of its structure. The understanding of these issues is fundamental to strategic investment decisions. The general characteristics of the bullion market is hereby followed by the analysis of the structure of its world demand and the related factors. The bullion demand for two basic products, i.e. bars and coins is subject to special analysis. Depending on the character of a given factor and availability of empirical data, the analysis relied on basic descriptive statistics, graphic charts and descriptive analysis. The completed analysis proves that there are material differences between the volume and structure of bullion demand and that the relations between the demand and price of both precious metals have not always reflected the tendencies defined in the literature.